Hydrogen storage in high surface area graphene scaffolds. Issue 83 (3rd September 2015) - Klechikov, Alexey; Mercier, Guillaume; Sharifi, Tiva; Baburin, Igor A.; Seifert, Gotthard; Talyzin, Alexandr V.
Abstract : Graphene scaffold materials with a surface area of ∼3300 m 2 g −1 showed hydrogen uptakes up to ∼7.5 wt% at 77 K. Abstract : Using an optimized KOH activation procedure we prepared highly porous graphene scaffold materials with SSA values up to 3400 m 2 g −1 and a pore volume up to 2.2 cm 3 g −1, which are among the highest for carbon materials. Hydrogen uptake of activated graphene samples was evaluated in a broad temperature interval (77–296 K). After additional activation by hydrogen annealing the maximal excess H2 uptake of 7.5 wt% was obtained at 77 K. A hydrogen storage value as high as 4 wt% was observed already at 193 K (120 bar H2 ), a temperature of solid CO2, which can be easily maintained using common industrial refrigeration methods.